Contribution of Teacher – Student Relationship and Self Regulation as a Mediator to Student's Risk Behavior - A'yun, Qurroti; Hanurawan, Fattah; Rahmawati, Hetti; Hitipiew, Imanuel (Bulletin of Counseling and Psychotherapy, 2024)
The research background highlights the increasing number of adolescents exposed to risk behaviors both in school environments and in society at large. This phenomenon is worsening. Thus, this study aims to examine whether the theoretical model of adolescent risk behavior aligns with empirical conditions in society. Additionally, the study examines the influence of variables within the model. The model is derived from Bronfenbrenner's ecological system theory (1994). This research was conducted using a quantitative approach with a correlational study design involving 628 adolescents aged 15-17 years from various demographic backgrounds, utilizing cluster sampling. Data collection was carried out using Google Forms. The study employs the adapted Teacher-Student Relationship Scale, Self-Regulation Scale, and Risk Behavior Scale, all validated through Confirmatory Factor Analysis, with analysis conducted using Structural Equation Modeling (SEM). The findings of this study conclude that environmental factors, specifically teacher-student relationships, have a significant influence on adolescent risk behavior and self-regulation. However, self-regulation does not have a significant influence on adolescent risk behavior. Furthermore, the teacher-student relationship does not have a meaningful influence on adolescent risk behavior through self-regulation as a mediator.